Значення військового однострою Збройних сил Західно-Української Народної Республіки як індикатора самоідентичності - Вовк, Наталія; Vovk, Nataliya (Lviv Politechnic Publishing House, 2019)
У статті проаналізовано особливості устрою військовиків Української галицької армії, основні розпізнавальні елементи військового однострою УГА. Подано характеристику єдиної форми для українського війська, відзнак за родом військ, старшинських відзнак тощо. Увагу також акцентовано на бойових відзнаках, медалях, які були частиною військового устрою.

The article analyzes the uniform and military distinctions in the armed forces, which discipline the personnel, substantially increase its moral and combat spirit, increase national consciousness, provide the continuity of generations, provide basis for the civil dignity of the warrior. The author reminds that the army of the Western Ukrainian People's Republic (ZUNR) is not an exception, as it was formed under the difficult conditions, already during the active armed hostilities in November 1918. The purpose of the research is to create an image of the soldiers of the Ukrainian Galician Army. In order to achieve this goal, it is necessary to perform the following tasks: to analyze the historiographical and source base; to define the basic analysis elements of the UGA soldiers’ appearance; to carry out the analysis of the main badges and military medals of the ZUNR troops; create an image of ZUNR army in historiographic view. To analyze the military uniform of the ZUNR armed forces, the author identified the main items of the UGA soldiers’ appearance. Such items are: cover (and/or cap sign), outerwear, shoes and distinguishing marks. As a cover, according to the study, they used a hat «mazepynka» consisting of a cap («holovach»), a decorative flap («obklada»), a poke («dashok»), a cap mark («vidznaka») and a button for fastening the flap. The bottom of the hat was flat and the hat itself consisted of eight wedges. The flap was sewn to the cap, which was fastened to the button. The edges of the hat were trimmed with a cloth colored in accordance to the soldier’s weapon. The hat sign was in the form of a silver (for ordinary soldiers and deputy-master sergeants) and gold (for master sergeant) circle. Analyzing the outer clothing of the UGA military, the author mentions the «blyuza», that is, a field-type garment, which was single-breasted, fastened to the buttons and had four pockets (upper ones were imposed, and the bottom ones were slit). Soldiers sewed chases on the shoulders of their blyuzes. Over the blyuzes, in the cold season, the warriors wore raincoats. The article shows that an important factor in the education of servicemen are the rewards – the promotion for the military merit in the battles of moral and material nature, as well as the reasonable initiative of conscience and diligence in the service during the peacetime. Therefore, the military and political leadership of the ZUNR introduced the award system of the Galician state. The author notes that the UGA had a well-designed system of the state affiliation signs, the types of weapons and specialties (the color of the hinges, armlets, cants), the categories (hinges) and the degree of the soldier (the number of struts on the sleeves), and in some cases even the unit, to which the soldier belongs (button with the number of the buttonhole). The color of the awards, including the cap signs, was different for the master and deputy-master sergeants and ordinary soldiers.
The meaning of the military uniform of the West Ukrainian people’s republic armed forces as a self-identicity indicator
Keywords: Західноукраїнська народна республіка (ЗУНР); Українська галицька армія (УГА); військовий однострій; військо; нагорода; медаль; Western Ukrainian People's Republic (ZUNR); Ukrainian Galician Army (UGA); military uniform; army; award; medal; © Вовк Наталія; 2019